Institutions Supporting Technical Advance in Industry - Nelson, Richard R. (American Economic Review, 2016)
elsewhere (1982), economists' beliefs that modern capitalism is a fine innovation-generating machine have no intellectual grounding in contemporary neoclassical theory. The twin theorems take technologies as given. The apparent effectiveness of capitalism in this arena must reside in characteristics and mechanisms other than those featured in the microeconomic theory textbooks. In our book, we attempt to analyze these. It also is true that the capitalist engine is a much more complicated one than many economists seem to think. I presently am